2020
DOI: 10.1186/s12915-020-00888-z
|View full text |Cite
|
Sign up to set email alerts
|

The selectivity filter of the mitochondrial protein import machinery

Abstract: Background The uptake of newly synthesized nuclear-encoded mitochondrial proteins from the cytosol is mediated by a complex of mitochondrial outer membrane proteins comprising a central pore-forming component and associated receptor proteins. Distinct fractions of proteins initially bind to the receptor proteins and are subsequently transferred to the pore-forming component for import. The aim of this study was the identification of the decisive elements of this machinery that determine the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 106 publications
2
23
0
Order By: Relevance
“…In our experiments, we found that an exchange of this residue for alanine (R192A) reduced the efficiency of Orf9b binding to TOM70 by about 50%. Remarkably, this effect corresponds to similar values with regard to the contribution of TOM70 in the import of proteins into the inner mitochondrial compartments [24,33,34]. For efficient import of nuclear-encoded proteins into mitochondria, TOM70 is not essential; however, it substantially facilitates the targeting of its substrate proteins.…”
Section: The Mechanisms Of Orf9b-tom70 Interactionsupporting
confidence: 58%
See 3 more Smart Citations
“…In our experiments, we found that an exchange of this residue for alanine (R192A) reduced the efficiency of Orf9b binding to TOM70 by about 50%. Remarkably, this effect corresponds to similar values with regard to the contribution of TOM70 in the import of proteins into the inner mitochondrial compartments [24,33,34]. For efficient import of nuclear-encoded proteins into mitochondria, TOM70 is not essential; however, it substantially facilitates the targeting of its substrate proteins.…”
Section: The Mechanisms Of Orf9b-tom70 Interactionsupporting
confidence: 58%
“…Using this system, we found that radiolabeled Orf9b associated with TOM70 (Figure 1C, lane 1). Under the same conditions, radiolabeled mouse dihydrofolate reductase (DHFR), a cytosolic protein of 21.6 kDa, often used as an established model protein [24][25][26], showed no binding to the receptor (Figure 1C, lane 2). Signals obtained after SDS-PAGE and autoradiographic detection were quantified using 2% of the total added lysate as internal control ("Load").…”
Section: A Phosphomimetic Amino Acid Exchange In Orf9b Prevents Its Interaction With Tom70mentioning
confidence: 99%
See 2 more Smart Citations
“…Tom40 is the central and channel-forming subunit of the TOM complex [ 3 , 21 ]. A wide range of important studies on protein import into mitochondria have shown that Tom40 is not only the entry gate for most mitochondrial precursor proteins delivered from the cytosol to various sub-mitochondrial locations [ 39 , 40 , 41 ] since it also works as a decisive general selectivity filter in the uptake of newly synthesized mitochondrial proteins [ 42 , 43 ]. Moreover, it was also proposed that the TOM complex can act as an insertase mediating lateral release of the membrane imported proteins into the outer membrane [ 44 ].…”
Section: Structure and Properties Of The Outer Membrane Protein Import Channelsmentioning
confidence: 99%